Phenotypic Analysis of Epilepsy in the Mitochondrial Encephalomyopathy, Lactic Acidosis, and Strokelike Episodes–Associated Mitochondrial DNA A3243G Mutation. (September 2014) - Demarest, Scott T.; Whitehead, Matthew T.; Turnacioglu, Sinan; Pearl, Phillip L.; Gropman, Andrea L.
The A to G mitochondrial DNA point mutation at position 3243 (A3243G) is the most common cause of mitochondrial encephalomyopathy, lactic acidosis, and strokelike episodes (MELAS), a systemic multiorgan disease. Epilepsy is a common finding but there is wide phenotypic variation that has not been thoroughly explored. We report the epilepsy phenotypes of 7 patients with the A3243G mutation. Most presented with typical MELAS and epilepsy characterized by infrequent prolonged focal seizures, including epilepsia partialis continua, hemiclonic status epilepticus, nonconvulsive status, and occipital status epilepticus. Seizures usually occurred during the acute phase of a strokelike episode. Periodic lateralized epileptiform discharges may be seen electrographically. Some patients with this mutation are completely asymptomatic or have mild symptoms typical for mitochondrial diseases. Slow spike-wave activity consistent with Lennox-Gastaut syndrome and electrographic status epilepticus was seen in 1 patient who responded to ethosuximide.